The role of prostaglandins in spontaneous and induced labour - Scher, Jonathan (Department of Obstetrics and Gynaecology, 2020)
The present investigation was undertaken in order to assess the clinical effects of prostaglandins and to evaluate their role in present modern day obstetrics. To this end pertinent clinical and laboratory studies were carried out. This has not been done before in the Republic of South Africa. It is considered that the following contributions to knowledge have been made: 1. In comparable patients prostaglandin F 2a and oxytocin are equally effective in labour induction at term. 2. Prostaglandin F2a is more effective in labour induction where the cervix is unripe and amniotomy is performed. 3. Amniotomy statistically significantly increases the success rate of induction of labour where prostaglandin F2a is used as the oxytocic agent. 4. Amniotomy statistically significantly accelerates labour in both prostaglandin F2a and oxytocin induction, using labour parameters for comparison which have been devised and are described in the text. 5. Comparable titration schedules of prostaglandin F2a and oxytocin have been devised for labour induction. 6. Prostaglandin F2a is not antidiuretic when used to induce patients with classical pre-eclampsia as compared with oxytocin. 7. Prostaglandins are implicated in the acceleratory phase of normal labour. 8. The only statistically significant side effect produced by prostaglandin F2a when compared with oxytocin is a transient red line in the skin along the area draining the site of the intravenous infusion. 9. Prostaglandin F2a does produce a coordinate form of labour if certain precautions are adhered to. 10. Effacement of the cervix in the latent phase has been measured and may be used in order to predict the rate of progress in the first stage of labour in primigravidae. The results are presented in the text.